2010
DOI: 10.1097/brs.0b013e3181dc9e0f
|View full text |Cite
|
Sign up to set email alerts
|

The Transfer of Disc Pressure to Adjacent Discs in Discography

Abstract: Discography of porcine discs induces a pressure increase in adjacent discs. A similar pressure transfer during human clinical discography might elicit false-positive pain reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…However, since intradiscal pressure during discography potentially is transferred to adjacent discs [28] and consequently might result in false positive diagnosis when pressurizing discs too much, a lower pressurization was used. O'Neill et al [17] also favors a lower pressurization when reporting 50 % false positive discograms at 25 psi above opening pressure.…”
Section: Limitationsmentioning
confidence: 99%
“…However, since intradiscal pressure during discography potentially is transferred to adjacent discs [28] and consequently might result in false positive diagnosis when pressurizing discs too much, a lower pressurization was used. O'Neill et al [17] also favors a lower pressurization when reporting 50 % false positive discograms at 25 psi above opening pressure.…”
Section: Limitationsmentioning
confidence: 99%
“…It has also been suggested that the injected contrast agent in itself may cause accelerated degeneration by inducing cell apoptosis [44]. In addition, it was recently demonstrated that discography-induced pressure increases not only in the injected disc, but also in adjacent discs potentially inducing false-positive responses [8][9][10]. This strongly questions the validity of discography as a tool-provoking pain on a single disc level only.…”
Section: Discussionmentioning
confidence: 97%
“…Discography remains, however, questioned due to factors such as inconclusiveness regarding false-positive responses, lack of ''gold standard'' and uncertainty of what actually causes the pain in or around the disc [3][4][5][6][7]. A recent finding that discography induces a significant pressure increase not only in the injected disc, but also in adjacent discs that further raises new questions about discography's validity [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…176 Additionally, it can be coated with radiopaque material to be used in x-ray studies. 176 Some studies reported its use in pigs, 177,178 rabbits, 179 and human cadaveric spines. 180 In the case of the Radi Medical Systems sensor, it was used to monitor intradiscal pressure in sedated pigs 181 and patients suffering from lumbar back pain.…”
Section: Intra-articular Pressurementioning
confidence: 99%